Pengaruh Kualitas Audit, Audit Tenure, dan Debt Default Terhadap Opini Audit Going Concern - Hidayah, Syafira Nurul; Agus Afandi (ARBITRASE: Journal of Economics and Accounting, 2024)
A going concern opinion received by a company indicates that there are conditions and events that raise auditors' doubts about the company's survival. A going concern audit opinion is an initial warning for users of financial reports, which is useful for avoiding mistakes in making decisions, especially in making investments. This research aims to determine the influence of audit quality, audit tenure and debt default on going concern audit opinion. The sample used in this research was service industry sector companies listed on the Indonesia Stock Exchange in 2018 – 2022. This sample was taken using a purposive sampling technique with sample data of 1,060 observations from the 212 companies sampled in this research. Hypothesis testing using logistic regression. The test results show that audit quality has a probability value of 0.0006 and debt default has a probability value of 0.0000, namely <0.05, which means that it partially has a significant effect on going concern audit opinion. Meanwhile, audit tenure has a probability value of 0.5161, namely > 0.05, which means that it partially has no significant effect on going concern audit opinion. Audit quality, audit tenure, and debt default simultaneously influence going concern audit opinion with a probability value (LR-statistic) of 0.000000 < 0.05.